Penggunaan Media Kartu Bergambar Untuk Meningkatkan Kemampuan Membaca Siswa Kelas I SDN 1 Gegerung Kecamatan Lingsar Kabupaten Lombok Barat - Mahyuni, Mahyuni; Muzakkir, Akhmad; Aziz, Lalu Abdul; Haryadi, Herjan (FONDASI: Jurnal Pendidikan Dasar, 2025)
This research aims to find out how to use picture card media to improve the reading skills of class I students at SDN 1 Gegerung, Lingsar District, West Lombok Regency. This type of research is classroom action research (PTK). The data collection techniques used are observation, performance tests, and documentation. The results showed a significant increase in teacher and student activity. Teacher activity in cycle I was in the sufficient category (70), cycle II in the good category (77.5), and increased to very good in cycle III (87.5). Meanwhile, student activity in cycle I was in the poor category (50.78), cycle II (63.15), and increased in cycle III with a good category (82.36). This shows that picture cards can improve the reading ability of class I students at SDN 1 Gegerung, Lingsar District, West Lombok Regency.